EUROPEANIZATION AND REFORMATION OF HIGHER EDUCATION SECTOR IN THE EASTERN PARTNERSHIP COUNTRIES THROUGH BOLOGNA PROCESS IN PURSUIT OF THE EUROPEAN INTEGRATION - Iryna SIKORSKA (Eastern European Journal of Regional Studies)
This article examines the critical role of higher education reforms in the Eastern Partnership (EaP) countries since their independence as they endeavor to align their systems with European standards and norms, ultimately seeking closer integration with the European Union (EU). The EaP countries, comprising Armenia, Azerbaijan, Belarus, Georgia, Moldova, and Ukraine, have embarked on ambitious journeys of transformation in their higher education sectors to foster economic development, enhance academic excellence, and strengthen regional cooperation. The article employs a comprehensive approach, encompassing both policy analysis and empirical insights to shed light on the multifaceted nature of higher education reforms across the region. It delves into the various challenges and opportunities faced by the EaP countries in their pursuit of European integration through higher education reforms. The key themes explored include the alignment of the national higher education reforms with the Bologna Declaration guidelines including the promotion of internationalization and quality assurance mechanisms emphasizing the importance of cross-border collaboration and knowledge exchange. It critically assesses the progress made so far, highlighting successes and identifying persistent obstacles. Moreover, it examines the role of international organizations and the EU programs in supporting these reforms. The analysis highlights the importance of higher education reforms in the EaP region not only as an instrument for achieving European integration but also as a catalyst for broader societal and economic transformations. The research data collected refer to the period of 1991-2020.